Ecology Based Stunting Prevention Model in The Floating Houses Along The Kahayan River, Palangka Raya City, Indonesia - Mars Khendra Kusfriyadi; I Nyoman Sudyana; Liswara Neneng; Trilianty Lestarisa (Jurnal Kesehatan Manarang, 2026)
Stunting continues to pose a significant public health concern in riverine and ecologically vulnerable communities, where environmental, socio-cultural, and health system factors converge. Populations residing in floating dwellings along the Kahayan River face challenges such as inadequate sanitation, exposure to unsafe water sources, and limited access to essential services, all of which may contribute to an elevated risk of stunting. Accordingly, a comprehensive analytical model is warranted to clarify both direct and indirect ecological pathways influencing stunting among children under five in floating-house settlements. This mixed method cross-sectional study was carried out among children aged 0–59 months residing in floating-house communities along the Kahayan River. A purposive sampling technique was employed to select a total of 193 research participants. Quantitative data were gathered through structured questionnaires and anthropometric assessments, and subsequently analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). Qualitative data were collected via in-depth interviews and focus group discussions with mothers, community leaders, healthcare professionals, and local stakeholders. Ecological determinants of stunting encompass individual-level factors such as dietary intake (β = 0.615, t = 12.871) and infectious diseases (β = 0.121, t = 2.370), both of which demonstrate direct impacts on stunting. Conversely, environmental sanitation (β = -0.096, t = 1.985) and cultural factors (β = -0.082, t = 1.665) are found to have indirect effects on stunting. Stunting among riverine floating communities is linked to ecological health factors. To prevent it effectively, a comprehensive approach is needed, including improved sanitation, culturally sensitive nutrition education, infection control, and strengthened community health services. The ecology-based model developed offers a tailored framework for sustainably reducing stunting in disadvantaged river settlements.